2015
DOI: 10.17524/repec.v9i2.1141
|View full text |Cite
|
Sign up to set email alerts
|

Quem está ficando para trás? Uma década de evasão nos cursos brasileiros de graduação em Administração de Empresas e Ciências Contábeis

Abstract: ResumoA evasão em Instituições de Ensino Superior (IES) públicas e privadas está associada com perdas sociais, acadêmicas e econômicas consideráveis. Essas perdas afetam toda a sociedade, já que os cidadãos pagam, direta ou indiretamente, pela sua própria educação e a dos seus familiares. O principal objetivo deste estudo foi analisar o comportamento de evasão dos estudantes matriculados nos cursos de graduação em Administração de Empresas e Ciências Contábeis em IES brasileiras entre 2001 e 2010. As taxas de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 20 publications
2
8
0
12
Order By: Relevance
“…2017 the undergraduate level" (Dias et al, 2010, p. 1). Th e prevalence of dropout, along with vacancies unfi lled in selection processes, results in social losses both to the students and the HEIs, because they mean unrealized opportunities and fi nancial expenditures that could be used otherwise (Cunha et al, 2014(Cunha et al, , 2015.…”
Section: Access To and Dropout From Higher Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…2017 the undergraduate level" (Dias et al, 2010, p. 1). Th e prevalence of dropout, along with vacancies unfi lled in selection processes, results in social losses both to the students and the HEIs, because they mean unrealized opportunities and fi nancial expenditures that could be used otherwise (Cunha et al, 2014(Cunha et al, , 2015.…”
Section: Access To and Dropout From Higher Educationmentioning
confidence: 99%
“…Among the situations that do not contribute to dropout, the respondents pointed out issues related to diffi culties in the professor-student relationship, supply of vacancies in the evening and the fact that some students live far from the HEIs. Cunha et al (2015) analyzed dropout among undergraduate students in the courses of Business Administration and Accounting Sciences in the Brazilian HEIs between 2001 and 2010 through data provided by the Brazilian National Institute of Educational Research and Study "Anísio Teixeira" (INEP) in 2012, in order to check the profi le of dropout and completion of the courses concerned. Th e results showed that dropout rates in the courses of Business Administration were higher than in the courses of Accounting Sciences, with rates of 16.24% and 12.45%, respectively.…”
Section: Access To and Dropout From Higher Educationmentioning
confidence: 99%
See 3 more Smart Citations